ROLE OF LAND USE PLANNING IN IMPROVING PUBLIC HEALTH: WAY FORWARD FOR MALAYSIA - Maidin, Ainul Jaria (PLANNING MALAYSIA, 2008)
It is an undeniable fact that land use planning regulatory framework and concern for improving living and built environment originated from the desire to improve public health, Planning issues remained at the root of some of the most intractable public health problems, including the declining rates of physical activity resulting from automobile-dependent environments or the isolation of poor and minority conmunities in areas plagued by environmental pollutants, violent crime, and high rates of disease. Land use, community design, and transportation systems substantially impact local air quality, water quality and supply, traffic safety, physical activity and exposure to contaminated industries. Mental health and quality of life issues also are profoundly affected by factors ranging fro1n the stress and difficulties of commuting to the presence or absence of natural areas and green spaces. There is a general realization that health specialists or planning departtnents cannot afford to operate in isolation from one another. This article intends to examine the important role that can be assumed by the members of local health department and other public health professionals in protecting local environmental health and improving the health of the communities through land use planning.